Energy assessment of solar technologies coupled with a ground source heat pump system for residential energy supply in Southern European climates. (November 2015) - Reda, Francesco; Arcuri, Natale; Loiacono, Pasquale; Mazzeo, Domenico
Abstract: The Directive 2010/31/EU and the Council of 19 May 2010 of the European Parliament focus, among other targets, on the reduction of the energy consumption of buildings. Solar technologies are often used in Southern European localities to contribute accomplishing this goal. The paper concentrates on the energy assessment of solar technologies, PV panels and solar thermal collectors, coupled with a ground source heat pump for different Italian localities, representative of Southern European climates. In particular, energy dynamic simulations have been done by means of TRNSYS software. Results have confirmed that injecting heat produced by means of the solar thermal collectors into the ground is a good procedure for saving energy in humid sub-tropical (Cfa) localities. Moreover, a compromise between the operations of the circulation pumps, responsible of supplying free ground cooling energy and of injecting solar thermal energy into the ground, has to be found in such localities. However, it can be generally concluded that the use of solar energy leads to low energy consumption especially in Csa localities (Rome and Palermo); where the use of small PV and solar thermal system allow important energy savings compared to the Cfa locality (Milan). Highlights: We analysed the energy performance of a SAGSHP for Southern European climates. We estimated the benefits of using PV and solar thermal energy in each climate. For short BHE how solar thermal energy is used affects the FGC in Cfa climate. Solar thermal energy has to be used differently according to the location. PV and solar thermal systems allow high energy savings compared in Csa climates.